2016
DOI: 10.2527/jas.2016-0632
|View full text |Cite
|
Sign up to set email alerts
|

Genome scan for postmortem carcass traits in Nellore cattle1

Abstract: Carcass traits measured after slaughter are economically relevant traits in beef cattle. In general, the slaughter house payment system is based on HCW. Ribeye area (REA) is associated with the amount of the meat in the carcass, and a minimum of backfat thickness (BFT) is necessary to protect the carcass during cooling. The aim of this study was to identify potential genomic regions harboring candidate genes affecting those traits in Nellore cattle. The data set used in the present study consisted of 1,756 Nel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 64 publications
1
25
0
Order By: Relevance
“…Endocytosis acts on the regulation of several processes, like cell adhesion and migration, extracellular signal transduction, cell growth and differentiation [45]. Junior et al [24] also found genes involved in cell cycle regulation and transportation of cellular substances associated with REA in Nellore cattle.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Endocytosis acts on the regulation of several processes, like cell adhesion and migration, extracellular signal transduction, cell growth and differentiation [45]. Junior et al [24] also found genes involved in cell cycle regulation and transportation of cellular substances associated with REA in Nellore cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with knockout mice for the NEDD4 gene showed that loss of NEDD4 reduced IGF-1 and insulin signaling, delayed embryonic development, and reduced growth and body weight [46]. Junior et al [24] in a GWAS study associated with REA, BFT and hot carcass weight found this gene enriched for the GO terms “cellular protein metabolic process” and “protein metabolic process” related to protein turnover and, consequently animal growth and development. In the present study, NEDD4 and NEDD4L were down-regulated in LowREA group, emphasizing their importance in regulating muscle growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fzd7 acts as a receptor for Wnt7a, and the signaling pathway comprising the two directly activates myogenic lineage progression at different stages [68]. In addition, Júnior et al used the BovineHD chip to correlate the carcass traits of Nellore cattle, finding that the REA (Ribeye area) trait was significantly associated with the bta8 (Bos taurus chromosome) 107978188bp-108270826bp region in cattle, which includes the CDKN2A gene [69]. In the comparison of 6-month-old with fetal (M-vs.-E) group the longissimus dorsi muscle methylation differential gene analysis, the steroid biosynthesis pathway was significantly enriched.…”
Section: Longissimus Dorsi Muscle Methylation Profile and Correlationmentioning
confidence: 99%